Magnetohydrodynamic modelling of star–planet interaction and associated auroral radio emission. Issue 4 (26th April 2020) - Turnpenney, Sam; Nichols, J D; Wynn, G A; Jia, X
ABSTRACT: We present calculations of auroral radio powers of magnetized hot Jupiters orbiting Sun-like stars, computed using global magnetohydrodynamic (MHD) modelling of the magnetospheric and ionospheric convection arising from the interaction between the magnetosphere and the stellar wind. Exoplanetary auroral radio powers are traditionally estimated using empirical or analytically derived relations, such as the radiometric Bode's law (RBL), which relates radio power to the magnetic or kinetic energy dissipated in the stellar wind–planet interaction. Such methods risk an oversimplification of the magnetospheric electrodynamics giving rise to radio emission. As the next step towards a self-consistent picture, we model the stellar wind–magnetosphere–ionosphere coupling currents using a 3D MHD model. We compute electron-cyclotron maser instability-driven emission from the calculated ionospheric field-aligned current density. We show that the auroral radio power is highly sensitive to interplanetary magnetic field (IMF) strength, and that the emission is saturated for plausible hot Jupiter Pedersen conductances, indicating that radio power may be largely independent of ionospheric conductance. We estimate peak radio powers of 10 14 W from a planet exposed to an IMF strength of 10 3 nT, implying flux densities at a distance of 15 pc from Earth potentially detectable with current and future radio telescopes. We also find a relation between radio power and planetary orbital distance that is broadly consistent with results from previous analytic models of magnetosphere–ionosphere coupling at hot Jupiters, and indicates that the RBL likely overestimates the radio powers by up to two orders of magnitude in the hot Jupiter regime.